Management of Slums and Dreaming of Slum - Free Cities: An Assessment of Policies and the Changes in India - MAHADEVA, Dr M. (The journal of contemporary issues in business and government, 2021)
Ever since the commencement of urbanization in India, slums have been co-existed in the urban areas, especially in the major cities. The incidence of slum is spread across almost all the states of the Union of India at varied levels. In fact, the number of slums and the incidence are at alarming level in the case of a group of states. The public efforts for development of the urban slums to make them human settlement friendly and then an integral part of urban life have had many setbacks. They mainly include the ad hoc approaches which were in vogue till the end of Tenth Five Year Plan. Lack of public policy commitment coupled with inadequate public finance, concerted efforts for the improvement of housing and living conditions of the slum dwellers have been the major impediments. But the national consensus evolved from late 90s heralded several initiatives to achieve slum-free urban India, which has brought considerable improvement. Under the windfall, slums have put up a decent level of achievements, in terms of the development of the living standard, access to housing amenities, degraded environment and marginalising the development gaps. Although slums have achieved better performance than their hosts (urban areas) but not only the overall development interventions must be stepped up but have to still go a long way. Achieving slum-free urban India is a gigantic task that needs huge investment not just from the government but also from others as well. Given the challenging considerations, this research offers a few policy implications like other corporate players part, integrated approach for both development of housing and amenities as well to improve the degraded environment, vigilant role of urban local bodies to mainstream the urban slums.